Anti-oxidative Effects of Butanol Seed Extract of Parkinsonia aculeata on Carbon Tetrachloride-Induced Liver Damage on Wistar Rats - Muhammad Bashiru AbdulRahman; Yusuf Gumburawa Malami; Sanusi Wara Hassan; Mansur Lawal; Waliu Temitope Adanlawo; Mansur Mohammed Birnin Kebbi; Kamaldeen Olalekan Sanusi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Medicinal plants have protective effect because of the presence of several compounds which have different mechanism of action. This study sought to assess the anti-oxidative effects of butanol seed extract of Parkinsonia aculeata on carbon tetrachloride (CCl4)-induced liver damage on Wistar rats. The Wistar rats were put into five groups, each with six rats: Group A received a daily dosage of liquid paraffin (1ml/kg); Group B received 1ml/kg body weight of CCl4 (30% in liquid paraffin intraperitoneal); Group C, D, and E received the seed extracts at 100, 120, and 160 mg/kg every day for two weeks. Induction of CCl4 was three times a week for two weeks simultaneously with the extract to the last day. After sacrificed, the liver was harvested and homogenized, and used for further analyses. There was a significant increase (p<0.05) in the levels of superoxide dismutase and catalase in all extract treated groups compared to positive control, except the catalase levels of group treated with 160mg/kg. Similar results was observed in vitamin C, vitamin E and glutathione in rats treated with 100 and 120mg/kg of the extract. The results of this study revealed that butanol seed extract from P. aculeata has antioxidant properties and can protect Wistar rats' livers from the damaging effects of CCl4.